Teach For America's paradoxical diversity initiative: Race, policy, and Black teacher displacement in urban schools - Terrenda C. White (Arizona State University, 2016)
This article examines the paradox of Teach For America's diversity gains and its support for policies that contribute to Black teacher decline in urban communities. TFA has countered claims that its expansion is connected to teacher displacement, but its two-pronged structure-as an alternative certification program and an influential policy actor via its leadership model for education reform-requires a critical analysis of the impact of its policy commitments on Black teachers. I propose steps to better align TFA's policy orientations with its diversity values by leveraging TFA's policy influence to support better working conditions for teachers in urban schools, democratic school turnarounds, and teacher organizing linked to broad social justice movements.